Suggestions for the Dates of Four Scottish Monuments - Boyle, Mary E (Proceedings of the Society of Antiquaries of Scotland, 1938)
The article is concerned with the dating of four sculptured stones from the church at Fowlis Webster, church of St Vigean’s near Arbroath, a chapel at Invergowrie, and the churchyard of Benvie. By closely examining the carvings and iconography on the sculptured stones, it is argued that the generally accepted early date of the stones is incorrect and they are in fact medieval.